Comparison of professional earnings of quota and non-quota students from Brazilian federal universities - José Roberto Abreu de Carvalho Junior; Wescley Silva Xavier; Marco Aurélio Marques Ferreira (Revista Eletrônica de Ciência Administrativa, 2024)
After 10 years of the policy of quotas at federal universities, the literature still lacks research on the inclusion of quota and non-quota graduates in the labor market. Faced with this problem, the aim of the article was to compare the gains in the labor market between quota holders and non-quota holders from undergraduate courses at Brazilian federal universities. For that, we applied an electronic questionnaire, which was answered by a significant sample of 11,458 graduates, from 248 undergraduate courses, from all areas of knowledge, from 18 federal universities and from the five regions of Brazil. Using the Chi-Square Test, we compared occupation status, the reason for not working, industry, type of position/job, remuneration, size of company/organization and occupation of leadership or management positions among graduates. The results suggest that quota holders graduates have high occupation rates, with a good insertion in the labor market, working in positions/jobs said to be more qualified, in large companies/organizations and receiving good remuneration. However, the results suggest that, in general, the occupational and salary earnings of quota holder graduates are still lower than those of non-quota holder graduates. Therefore, our results suggest that the quota policy of federal universities is an important tool for the socioeconomic inclusion of quota students, justifying its existence, but that it, by itself, still does not completely eliminate the strong social inequality among Brazilian families, which seems to affect differently the earnings of professionals in the labor market.